Programas de pesquisa em ciência da informação : análise na produção dos programas de pós-graduação brasileiros - Melo, Maytê Luanna Dias de (2023)
The history of science is, above all, the history of scientific research programs, which are ins-tituted by methodological guidelines that guide scientists in their practice, pointing out the paths of investigation that should be avoided and the paths that should be pursued. In view of this, it was conjectured that the auxiliary theories of Information Science make up the protec-tive belt and establish themselves in empirically progressive research programs. Thus, this study analyzes the Information Science research programs in Brazil, taking as references the main and auxiliary theories, which make up the defended theses and the contribution of Araú-jo (2018). From this perspective, it specifically seeks to map the set of hypotheses that make up the scientific production of Information Science in Brazil; describe the themes addressed in this production; identify the theoretical and methodological contributions adopted; highlight the research programs present in the studies, and; understand the theoretical and methodologi-cal progressive and/or regressive dynamics of this field. Procedurally, we opted for explora-tory-descriptive research with a hybrid, quali-quantitative approach, carried out through a bibliographic survey. Data were collected from the perspective of the Methodology of Scienti-fic Research Programs (MPPC) by Lakatos (1979), in the doctoral theses of the Brazilian Graduate Programs in Information Science available at the Digital Library of Theses and Dis-sertations (BDTD) maintained by the Brazilian Institute of Information in Science and Technology (IBICT). It was found that the theoretical and methodological contributions adop-ted in the analyzed scientific production have a progressive theoretical dynamic. It is conside-red that the set of theories that make up the scientific production of Information Science in Brazil has circumscribed affirmative heuristics that state that the protective belt of the area is constituted in the contemporary theoretical domains systematized by Araújo (2018), namely, scientific production and communication; representation and organization of Information; studies on informational subjects; information and knowledge management; political econo-my of information; metric studies of information; and memory, heritage and document. Ho-wever, most of the defended theses do not expressly explain their theoretical references, but pondering the themes addressed and the literature reviews that served as a basis for the opera-tionalization of these researches.